Democratic Citizenship and Its Changes as Empirical Phenomenon - Moro, Giovanni (SocietàMutamentoPolitica, 2016)
The article aims to contribute to the empirical approach towards the study of democratic citizenship, while avoiding both reductionist and all-embracing uses of the concept. It deals with three issues: the identification of the phenomenon, the observation of the dynamics of change, and the assessment of the ongoing evolutions of citizenship.